The HUBUNGAN PERSEPSI MAHASISWA TERHADAP MATA KULIAH DENGAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN - Damanhuri Damanhuri; Yuyu Yuhana (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
ABSTRACT Citizenship Education (PKn) has a very important role, through Civics courses it is hoped that it will be able to form students who have national insight and homeland ideals. The purpose of this research is to determine the relationship between student perceptions of courses and Civics learning achievement. The research hypothesis is that there is a relationship between student's perceptions of the course and their civics learning achievement. The method in this research is a survey using correlation techniques. The entire research population consisted of 1st-semester students in the Primary School Teacher Education study program, FKIP, Sultan Ageng Tirtayasa University, Class of 2022/2023. The sample was obtained using a proportional random sampling system taking 30% of the population. Based on the results of data analysis, shows that the more positive a student's perception of a course is, the higher their learning achievement tends to be with a correlation coefficient of 0.658. It can be concluded that Civics learning achievement can be improved by building students' positive attitudes towards the subject.